Benthic bacteria communities of coral reefs are shaped by sediment properties rather than coral trophic state - Ana Olmos Pin; Graeme F. Clark; Raphael Burkart-Radtke; Jakob Quade; Stephanie G. Gardner (PLoS ONE, 2026)
Understanding how different reef components contribute to ecosystem stability and function is crucial for assessing the health of reefs. Reef sediments and their associated bacteria are essential for reef productivity and stability, but are often overlooked in reef assessments. Here we examined bacterial communities and environmental properties in sediments closely associated with the coral Porites lutea , compared to those in adjacent sediment controls at One Tree Island Reef, and used incubation chambers to assess metabolic rates and nutrient availability. We found that seawater enclosed in the chamber containing P. lutea coral-associated sediment exhibited significantly higher gross photosynthetic and respiration rates than seawater enclosed in the chamber as sediment only controls, and the coral-associated bacterial assemblages within the sediment had higher alpha diversity and richness metrics. Additionally, bacterial communities were primarily shaped by total nitrogen, which was the strongest predictor of microbial community. Differential abundance analyses identified the families Woeseiaceae, Pirellulaceae, and Streptomycetaceae increased with higher photosynthetic and respiratory activity, whereas Rhodobacteraceae and Alteromonadaceae showed contrasting responses to carbon and nitrogen content. Together, these results suggest reef sediment bacterial assemblages were primarily structured by sediment properties and benthic productivity, rather than coral trophic state. This highlights the role of sediment physicochemical gradients in shaping and maintaining microbial diversity and ecosystem function.